Quality evaluation of government open data sets in Argentina using the HEVDA Validation Tool - Martínez, Roxana; Pons, Claudia; Rodríguez, Rocío; Vera, Pablo (Journal of Science and Research, 2021)
This work consists of measuring the quality of the datasets available on the web portal of the official public and national site of the country of Argentina. This research proposes to carry out a quality study applying the Open Data Quality Validation Tool (HEVDA), this tool implements quality metrics that measure the selected dataset, which results in an analysis of the flaws detected in it; for example, it allows detecting if there are errors, incomplete records, types of redundancy, etc. To explain the framing of this work, a survey of the aspects that are involved in this context is shown: open government, open public data, as well as government transparency. On the other hand, it shows the importance of maintaining the quality of the shared data, since it will be reused in different data sources and software, so this research focuses on the necessary aspects that favor the reading and understanding of the data sets published on government portals, which allows generating public opinion and showing traceability of the management of government resources.